2020
DOI: 10.1109/tnse.2018.2862919
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Spatial Arrangement Shapes Effective Connectivity Traits of in vitro Cortical Networks

Abstract: We studied effective connectivity in rat cortical cultures with various degrees of spatial aggregation, ranging from homogeneous networks to highly aggregated ones. We considered small cultures 3 mm in diameter and that contained about 2000 neurons. Spatial inhomogeneity favored an increase of metric correlations and connectivity among neighboring neurons. Effective connectivity was determined from spontaneous activity recordings using calcium fluorescence imaging. We used generalized transfer entropy as tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 49 publications
(86 reference statements)
4
52
0
Order By: Relevance
“…We explored in silico neuronal networks with spatial constraints by considering different sets of obstacles arranged on a circular area of either 2 or 4 mm in diameter. This size was selected to mimic the characteristic size of small in vitro cultures (Orlandi et al, 2013 ; Tibau et al, 2020 ). In the simulations, neurons were laid out on the surface in a homogeneous manner and connected to one another following a geometric model as in Orlandi et al ( 2013 ), in which the axons grew as concatenated segments according to a biased random walk ( Figure 1A ) and that is known to mimic well the behavior of individual axons (Feinerman et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We explored in silico neuronal networks with spatial constraints by considering different sets of obstacles arranged on a circular area of either 2 or 4 mm in diameter. This size was selected to mimic the characteristic size of small in vitro cultures (Orlandi et al, 2013 ; Tibau et al, 2020 ). In the simulations, neurons were laid out on the surface in a homogeneous manner and connected to one another following a geometric model as in Orlandi et al ( 2013 ), in which the axons grew as concatenated segments according to a biased random walk ( Figure 1A ) and that is known to mimic well the behavior of individual axons (Feinerman et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our simulations reflect the importance of metric correlations in shaping connectivity and dynamics in neuronal circuits. Metric correlations appear naturally in spatially embedded networks (Orlandi et al, 2013 ; Tibau et al, 2020 ). As in our simulations, other studies pointed out the spatial distribution of neurons and the characteristic axonal length relative to system size as central ingredients in shaping local and global structural traits (Schmeltzer et al, 2014 ; Hernández-Navarro et al, 2017 ; Okujeni et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] Recent studies showed that spatial embedding in these systems naturally feature metric correlations that shape in great measure the architectural and dynamic traits of the neuronal network. 14,[16][17][18] To the best of our knowledge, there exist no computational studies for damage that take into account the spatial embedding of biologically-realistic neuronal microcircuits. Thus, in the present study, we aim at lling this gap by introducing a detailed numerical exploration of the di erences between targeted attack and failure in spatially-embedded networks.…”
Section: Articlementioning
confidence: 99%